1999
DOI: 10.1042/bst027a078
|View full text |Cite
|
Sign up to set email alerts
|

PI 3-kinase effector molecules

Abstract: The universal role of 3-phosphorylated inositol lipids in cellular signal transduction has become apparent over the last few years. Of these lipids phosphatidylinositol 3,4,5-trisphosphate (PIP,) has aroused the most interest as a potential second messenger'. On aspect of our work is directed at identifying in vivo PIP' receptors in order to characterise the downstream pathways that become activated following PIP, production. Experimentally we have identified various proteins based initially on their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…3d and SI Movie 1). By contrast, no redistribution of Rasa3-GFP was detected in the presence of Bt 2 Ins(1,2,4,5)P 4 / PM, which has a Ϸ100-fold lower affinity for Rasa3 PH domain than Ins(1,3,4,5)P 4 (19) or in the presence of DMSO, both used as negative controls (Fig. 3d and SI Movies 2 and 3).…”
Section: Itpkb and Ins(1345)p4 Control Erk Activation And Bim Levementioning
confidence: 81%
See 1 more Smart Citation
“…3d and SI Movie 1). By contrast, no redistribution of Rasa3-GFP was detected in the presence of Bt 2 Ins(1,2,4,5)P 4 / PM, which has a Ϸ100-fold lower affinity for Rasa3 PH domain than Ins(1,3,4,5)P 4 (19) or in the presence of DMSO, both used as negative controls (Fig. 3d and SI Movies 2 and 3).…”
Section: Itpkb and Ins(1345)p4 Control Erk Activation And Bim Levementioning
confidence: 81%
“…18 and http://symatlas.gnf.org/ SymAtlas). The protein is essentially membrane-associated through the interaction of its PH domain with phosphatidylinositol 4,5-bisphosphate (19). Because Rasa3 PH domain has also a high affinity for the water-soluble Ins(1,3,4,5)P 4 (20,21), it has been suggested that Ins(1,3,4,5)P 4 production in stimulated thymocytes could result in a substantial redistribution of Rasa3 from the plasma membrane to the cytosol, allowing unhindered Ras activation (7).…”
Section: Itpkb and Ins(1345)p4 Control Erk Activation And Bim Levementioning
confidence: 99%
“…The mechanism of PI influence on the AP properties in the reverse micelles can be explained as a result of complex formation between inositol lipids and proteins. Indeed, some proteins have specific binding domains for inositol lipids, which might regulate their activity [35][36][37][38]. In the case of AP, the formation of such complex in aqueous solution was recently confirmed [27].…”
Section: Influence Of Membrane Composition On Catalytic Activity Of Amentioning
confidence: 92%
“…Although this domain structure is conserved, subtle variation in the function of each individual domain and the interaction between domains has a pronounced effect on the regulation of each protein (9,11,12,14,15). For GAP1 IP4BP and GAP1 m , the association of phosphoinositides with their pleckstrin homology domains is an important determinant in targeting these proteins to the cytosolic leaflet of the plasma membrane where they inactivate Ras (11,16,17). In the case of CAPRI and RASAL, plasma membrane targeting is driven through their tandem C2 domains, which bind phospholipids upon an elevation in the intracellular free Ca 2ϩ concentration ([Ca 2ϩ ] i ) (12,14,15).…”
mentioning
confidence: 99%